For love of the game [videorecording (DVD)] - Raimi, Sam; Costner, Kevin; Preston, Kelly; Reilly, John C., 1965-; Shaara, Michael (Universal Home Video, 2000)
At the end of a disappointing season, legendary Detroit Tigers pitcher Billy Chapel may be at the end of his career and relationship when he plays the game of his life.